2009
DOI: 10.1038/sj.bjc.6604937
|View full text |Cite
|
Sign up to set email alerts
|

Association of constitutively activated hepatocyte growth factor receptor (Met) with resistance to a dual EGFR/Her2 inhibitor in non-small-cell lung cancer cells

Abstract: There is a pressing need to identify new drug targets and novel approaches for treatment of non-small-cell lung carcinoma (NSCLC). Members of the epidermal growth factor receptor (EGFR) and Met receptor families have been identified as important molecular targets for NSCLC. Two EGFR tyrosine kinase inhibitors (TKIs; erlotinib and gefitinib) are in current clinical use, but a majority of patients do not respond to these targeted therapies. We used receptor TK (RTK) capture arrays to identify receptors active in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 34 publications
1
67
0
1
Order By: Relevance
“…In non-small cell lung cancer cells, MET overexpression increases EGFR downstream signaling, and the combined use of dual EGFR/HER2 and MET tyrosine kinase inhibitors results in maximal growth inhibition. 43 Conversely, Qi et al 44 have reported that resistance to MET kinase inhibitors in gastric cancer cells develops via activation of the EGFR pathway. In a recent tumor-xenograft study, simultaneous targeting of MET and EGFR pathways provided synergistic inhibitory effects in breast, lung and pancreatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer cells, MET overexpression increases EGFR downstream signaling, and the combined use of dual EGFR/HER2 and MET tyrosine kinase inhibitors results in maximal growth inhibition. 43 Conversely, Qi et al 44 have reported that resistance to MET kinase inhibitors in gastric cancer cells develops via activation of the EGFR pathway. In a recent tumor-xenograft study, simultaneous targeting of MET and EGFR pathways provided synergistic inhibitory effects in breast, lung and pancreatic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MET was reported to interact with both EGFR and HER2. 36 These results suggest that cross talk between the EGFR pathway and the MET pathway might occur in Group I cell lines, and that co-activation of EGFR and MET might be associated with genetic abnormalities of EGFR, MET, and HER2. Ϫ6 mol/L) suppressed the expressions and phosphorylation of both EGFR and MET in HCC827 and Calu-3.…”
Section: Hierarchical Cluster Analysis Of Cell Linesmentioning
confidence: 75%
“…Prolonged Met signaling most probably constitutes the tumor-promoting properties of HGF, which include, in addition to invasion, cellular proliferation, survival, actin remodeling and motility (Birchmeier et al, 2003;Gentile et al, 2008). Met overexpression and activating mutations are strongly associated with aggressive cancers, including carcinomas of breast, prostate, lung, brain, gastric and pancreatic origin (Agarwal et al, 2009;Sawada et al, 2007;Taniguchi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%